The Reality of Application of Governance at Jerash University from the Point of View of Faculty Members - Adnan Mufleh Mohammed (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
The current study aims to identify the degree of application of governance at Jerash University from the point of view of the faculty members. In order to achieve the objectives of the study, a questionnaire consisting of (30) items distributed on three areas: (accountability, transparency, and participation in decision-making) was applied to a randomly chosen sample of (120) faculty members at Jerash University. The results of the study showed that the reality of applying governance at University of Jerash from the point of view of the study sample in general was moderately high. The results also showed that there were no statistically significant differences in the average estimates of the study sample members in the degree of application of governance at Jerash University due to the categorical study variables in all fields, except for the type of college. The study recommends the application of governance in all Jordanian universities, and recommends annual review of university governance systems and concepts and the extent of their application in order to amend ineffective items.